M2b macrophages stimulate lymphangiogenesis to reduce myocardial fibrosis after myocardial ischaemia/reperfusion injury - Cuiping Wang; Yuan Yue; Suiqing Huang; Keke Wang; Xiao Yang; Jiantao Chen; Jiaxing Huang; Zhongkai Wu (Taylor & Francis Group, 2022)
Context Therapeutic lymphangiogenesis is a new treatment for cardiovascular diseases. Our previous study showed M2b macrophages can alleviate myocardial ischaemia/reperfusion injury (MI/RI). However, the relation between M2b macrophages and lymphangiogenesis is not clear. Objective To investigate the effects of M2b macrophages on lymphangiogenesis after MI/RI. Materials and methods Forty male Sprague-Dawley (SD) rats were randomized into Sham operation group (control, n = 8), MI/RI group (n = 16) and M2b macrophage transplantation group (n = 16). M2b macrophages (1 × 106) in 100 μL of normal saline or the same volume of vehicle was injected into the cardiac ischaemic zone. Two weeks later, echocardiography and lymphatic counts were performed, and the extent of myocardial fibrosis and the expression of vascular endothelial growth factor C (VEGFC) and VEGF receptor 3 (VEGFR3) were determined. In vitro, lymphatic endothelial cells (LECs) were cultured with M2b macrophages for 6-24 h, and the proliferation, migration and tube formation of the LECs were assessed. Results In vivo, M2b macrophage transplantation increased the level of lymphangiogenesis 2.11-fold, reduced 4.42% fibrosis, improved 18.65% left ventricular ejection fraction (LVEF) and upregulated the expressions of VEGFC and VEGFR3. In vitro, M2b macrophage increased the proliferation, migration, tube formation and VEGFC expression of LECs. M2b macrophage supernatant upregulated VEGFR3 expression of LECs. Discussion and Conclusions Our study shows that M2b macrophages can promote lymphangiogenesis to reduce myocardial fibrosis and improve heart function, suggesting the possible use of M2b macrophage for myocardial protection therapy.